Two Convergence Results for Inexact Orbits of Nonexpansive Operators in Metric Spaces with Graphs - Alexander J. Zaslavski (Axioms, 2023)
In this work we show that if iterates of a nonexpansive self-mapping of a complete metric with a graph converge uniformly on a subset of the space, then this convergence is stable under the presence of small computational errors.